ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2021
DOI: 10.1109/icassp39728.2021.9414255
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Source Model Learning for Determined Source Separation

Abstract: We propose to learn surrogate functions of universal speech priors for determined blind speech separation. Deep speech priors are highly desirable due to their superior modelling power, but are not compatible with state-of-the-art independent vector analysis based on majorization-minimization (AuxIVA), since deriving the required surrogate function is not easy, nor always possible. Instead, we do away with exact majorization and directly approximate the surrogate. Taking advantage of iterative source steering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
(56 reference statements)
0
4
0
1
Order By: Relevance
“…( 1 ) 音源分離における空間フィルタをニューラルネットワー クによって推論 (112)(113) ( 2 ) ブラインド音源分離の音源モデルへの深層学習の導 入 ( 114) - (120) ( 3 ) 位相差などの複数マイクロホンの信号から得た情報を ニューラルネットワークの特徴量として利用 (103)(121) ( 4 ) ビームフォーミングで用いる共分散行列をニューラル ネットワークを介して求めた時間周波数マスクを用いて 推定 (122)…”
Section: の様々な組み合わせ方が検討されている.unclassified
“…( 1 ) 音源分離における空間フィルタをニューラルネットワー クによって推論 (112)(113) ( 2 ) ブラインド音源分離の音源モデルへの深層学習の導 入 ( 114) - (120) ( 3 ) 位相差などの複数マイクロホンの信号から得た情報を ニューラルネットワークの特徴量として利用 (103)(121) ( 4 ) ビームフォーミングで用いる共分散行列をニューラル ネットワークを介して求めた時間周波数マスクを用いて 推定 (122)…”
Section: の様々な組み合わせ方が検討されている.unclassified
“…Let a k,i t be the mixing vector after i deflation steps computed on the tth block via (8). Due to the orthogonality of w k,i and a k,i t , the subtraction is achieved through…”
Section: E Re-estimation Of the Soi On Extraction Failure: Deflationmentioning
confidence: 99%
“…The recovered frequency components have a random order and all components corresponding to the wide-band source need to be identified in order to reconstruct it in the time-domain. To alleviate this drawback, the independent vector analysis (IVA, [7], [8]) has been proposed. It binds together the frequency components corresponding to a single source using higherorder dependencies among them.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that DNNs can estimate statistics to control step-sizes [61], [62] or estimate entire updates [63] for a single-channel AEC. Similarly, past work has used DNNs to predict updates for the internal statistics of multi-channel beamformers [64] and to learn source-models for multi-channel source separation [65]. These works differ from hybrid approaches in that they leverage neural networks to update or control AFs directly and thus focus on improving the performance of AFs themselves.…”
Section: Introductionmentioning
confidence: 99%